Impact of resistance to fenitrothion and esfenvalerate on the control of Rhyzopertha dominica (Coleoptera: Bostrichidae) in stored wheat. (2020)
Insecticides resistance can significantly compromise the control programs of Rhyzopertha dominica (Coleoptera: Bostrichidae), one of the main wheat pests in warehouses. The objectives of this work were to study the occurrence of resistance to fenitrothion and esfenvalerate in two Brazilian populations of R. dominica from Santa Rosa (SR lineage) and Campo Grande (CG lineage), as well as the insecticidal effect and residual action of these insecticides when used alone or as a mixture in stored wheat. The application system was calibrated to provide grain treatment at theoretical concentrations of 10 and/or 0.5 mg kg-1 fenitrothion and esfenvalerate, respectively. By comparing the fitted mortality curves for lineages within insecticides, as well as insecticides within lineages significant differences were observed in all cases. Esfenvalerate was ineffective in controlling R. dominica. The SR lineage of R. dominica was more resistant to the insecticides tested than the CG lineage. The number of individuals in the F1 offspring of R. dominica was dependent on the lineage, insecticide, and on the time after the application of insecticide. In the untreated grains (control), the CG lineage had a greater number of progeny than the SR lineage, while the opposite was verified in the grains treated. Fenitrothion and esfenvalerate are not useful for the control of R. dominica. Factors influencing control of R. dominica are discussed in this work.